Contrasting Reactivity of CS2 with Cyclic vs. Acyclic Amidines. Issue 33 (21st October 2015) - Ang, M. Trisha C.; Phan, Lam; Alshamrani, Aliyah K.; Harjani, Jitendra R.; Wang, Ruiyao; Schatte, Gabriele; Mosey, Nicholas J.; Jessop, Philip G.
Abstract: The interaction between carbon dioxide (CO2 ) and amidines such as 1, 8‐diazabicyclo[5.4.0]undecane (DBU) has been extensively studied, but the reaction of isovalent CS2 with such bases has been largely ignored, apart from a single crystallography report. Acyclic acetamidines are cleaved by CS2 at room temperature to give an isothiocyanate and a thioacetamide. Because the pathway to that cleavage involves a rotation that is difficult for cyclic amidines, the reaction of CS2 with cyclic amidines produces an entirely different product: a cyclic carbamic carboxylic trithioanhydride structure. The path to that product involves sp 3 C‐H activation leading to the formation of a new C–C bond at a carbon α to the central carbon of the amidine group. Alkylation and ring‐opening of the cyclic carbamic carboxylic trithioanhydride has also been demonstrated under ambient conditions. Abstract : Cyclic amidines react readily with CS2 to create new carbamic carboxylic trithioanhydride rings but acyclic amidines cleave the C=N bond and give isothiocyanates instead.